Role of rivaroxaban in the prevention of atherosclerotic events. Issue 8 (3rd August 2019) - Sanmartín, Marcelo; Bellmunt, Sergi; Cosín-Sales, Juan; García-Moll, Xavier; Riera-Mestre, Antoni; Almendro-Delia, Manuel; Hernández, José Luis; Lozano, Francisco; Mazón, Pilar; Suarez Fernández, Carmen
ABSTRACT: Introduction : The current approach of using only antiplatelet therapy for secondary prevention leaves a substantial risk of recurrent cardiovascular complications and mortality. Areas covered : In this manuscript, the role of coagulation in atherothrombosis is reviewed, as well as the impact of vascular doses of rivaroxaban on major cardiovascular outcomes and major adverse limb events. Expert opinion : In COMPASS, among patients with coronary heart disease and/or peripheral artery disease, compared to aspirin, the addition of rivaroxaban 2.5 mg twice daily to aspirin, significantly reduced the risk of major atherosclerotic outcomes, cardiovascular death and death for any cause, with a significant increase in the risk of major bleeding, but not fatal or intracranial bleedings. Preclinical data strongly suggest that rivaroxaban exerts vascular protection through different mechanisms, including improvement of endothelial functionality and fibrinolytic activity at endothelium, anti-inflammatory properties, and platelet-dependent thrombin generation. All these data indicate that among patients with atherosclerotic vascular disease, the addition of rivaroxaban 2.5 mg may provide further vascular protection.